Sr(Cr0.2Mn0.2Fe0.2Co0.2Ni0.2)O3: A novel high-entropy perovskite oxide with enhanced electromagnetic wave absorption properties - Mengru Li; Qing Zhi; Jinlu Li; Chengwen Wu; Xuewen Jiang; Zhiyu Min; Rui Zhang; Hailong Wang; Haibin Wang; Bingbing Fan (Journal of Materiomics, 2024)
Perovskite materials (ABO3) possess a wealth of elements selectable and exhibit a diverse range of octahedral transformations. The emergence of high-entropy perovskite ceramics provides a fresh perspective for advancing the field of wave-absorbing materials. In this study, we concentrate on the wet chemical synthesis of a high-entropy perovskite oxide, Sr(Cr0.2Mn0.2Fe0.2Co0.2Ni0.2)O3, and investigate its crystal structure, microstructure, chemical composition, magnetic properties, and microwave absorbing capabilities. The results indicate that when sintered at a temperature of 1,350 °C, the sample achieves a minimum reflection loss of −54.0 dB at a frequency of 9.68 GHz, accompanied by a maximum effective absorption bandwidth (EAB) of 7.44 GHz at the thickness of 1.8 mm. The high-entropy design of the B-site induces distortions of oxygen vacancy and octahedral structure of the perovskite material. This leads to the fine tuning of its dielectric and magnetic properties, thereby endowing perovskite with excellent electromagnetic wave absorption capabilities. Consequently, perovskite emerges as a promising new electromagnetic wave absorption material with significant potential.